2021
DOI: 10.1029/2020jc017001
|View full text |Cite
|
Sign up to set email alerts
|

What Role Does the Barrier Layer Play During Extreme El Niño Events?

Abstract: In most regions of the ocean, the mixed layer depth (MLD) determined by the density stratification is the same as the isothermal layer depth (ILD). However, when the ILD is deeper than the MLD, a "barrier layer" (BL) exists (Lukas & Lindstrom, 1991) that can inhibit the vertical mixing of cold water from below into the mixed layer (Godfrey & Lindstrom, 1989) as well as trap the incoming solar radiation to a shallower surface layer. BLs can form for a variety of reasons: as a result of heavy rainfall, especiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
(78 reference statements)
1
9
0
1
Order By: Relevance
“…X. Zhang et al. (2021) quantified thermohaline effects on zonal currents at 165°E and found that the salinity effect is a major cause of variability in zonal current anomalies at the edge of the western Pacific fresh and warm pool. Chakraborty et al.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…X. Zhang et al. (2021) quantified thermohaline effects on zonal currents at 165°E and found that the salinity effect is a major cause of variability in zonal current anomalies at the edge of the western Pacific fresh and warm pool. Chakraborty et al.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang & Busalacchi, 2009; R.‐H. Zhang et al., 2012; Zheng et al., 2014; Zhi, Zhang, Lin, & Yu, 2019), and the other with pressure gradients associated with density (G. C. Johnson et al., 2002; X. Zhang et al., 2021). Among the two influence pathways, less attention has been paid to the salinity role in modulating currents (the pathway with pressure gradients due to salinity effect on density).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Os processos naturais que ocorrem na camada da atmosfera terrestre, os chamados fenômenos atmosféricos, como El Niño e La Niña, conhecidos como o fenômeno El Niño Oscilação Sul (ENOS) têm em comum o fato de originarem-se no Oceano Pacífico e trazerem consequências para o clima de todo o mundo, embora de formas diferentes. Quanto a sua formação, sabe-se que é resultante das interações anômalas entre ar e mar que ocorrem irregularmente no Oceano Pacífico Equatorial, pois ocorre o aquecimento das águas que, junto com os ventos alísios em baixos níveis, ocasiona um represamento das águas quentes no oeste do Oceano Pacífico (Zhang et al, 2021;Glantz, 2015;Andrade, 2011).…”
Section: Introductionunclassified